2020
DOI: 10.3390/microorganisms8030337
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Microbial Dissolved Organic Sulfur Transformations in Coastal Waters

Abstract: The marine trace gas dimethylsulfide (DMS) is the single most important biogenic source of atmospheric sulfur, accounting for up to 80% of global biogenic sulfur emissions. Approximately 300 million tons of DMS are produced annually, but the majority is degraded by microbes in seawater. The DMS precursor dimethylsulfoniopropionate (DMSP) and oxidation product dimethylsulphoxide (DMSO) are also important organic sulfur reservoirs. However, the marine sinks of dissolved DMSO remain unknown. We used a novel combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Measurements of DMS yield [80][81][82][83] vary widely (1-45%) depending on the region and the seasonal stage of the phytoplankton growth cycle. We note that DMS can also be produced by bacterial reduction of DMSO, the conversion by-product of DMS due to photolytic or bacterial oxidation [84], however the amount of DMS produced via this process does not seem to be significant [85].…”
Section: Role Of Heterotrophic Organismsmentioning
confidence: 80%
“…Measurements of DMS yield [80][81][82][83] vary widely (1-45%) depending on the region and the seasonal stage of the phytoplankton growth cycle. We note that DMS can also be produced by bacterial reduction of DMSO, the conversion by-product of DMS due to photolytic or bacterial oxidation [84], however the amount of DMS produced via this process does not seem to be significant [85].…”
Section: Role Of Heterotrophic Organismsmentioning
confidence: 80%
“…Some studies showed that it could be directly synthesized in marine phytoplankton cells (Simó et al, 1998;Lee et al, 1999). A recent study suggested that dissimilation of dissolved DMSO (DMSO d ) to carbon dioxide can be a significant loss pathway in coastal waters (Dixon et al, 2020). Both DMSP and DMSO exert similar intracellular functions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Both DMSP and DMSO exert similar intracellular functions (e.g. cryoprotection and antioxidation) in phytoplankton cells (Simó et al, 1998;Sunda et al, 2002) and can support bacterial carbon and sulfur demand (Simó et al, 2002;Dixon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, several time-series studies of DMS from different open ocean and coastal sites, such as the North Sea, the Atlantic Ocean and the Indian Ocean, have been conducted during the past years (see e.g. (Turner et al, 1996;Dacey et al, 1998;Shenoy and Patil, 2003;Vila-Costa et al, 2008;Dixon et al, 2020). However, the distributions and cycling of sulphur compounds in the Baltic Sea are still largely unknown, and only a few studies of DMS were carried out in the Baltic Sea (Leck et al, 1990;Leck and Rodhe, 1991;Orlikowska and Schulz-Bull, 2009).…”
Section: Introductionmentioning
confidence: 99%